Surface Modification of Erythrocytes with Lipid Anchors: Structure–Activity Relationship for Optimal Membrane Incorporation, in vivo Retention, and Immunocompatibility. Issue 8 (10th August 2022) - Gaikwad, Hanmant; Wang, Guankui; Li, Yue; Bourne, David; Simberg, Dmitri
Abstract : Surface Modification In article number 2200037, Dmitri Simberg and co‐workers synthesize a library of fluorescent Cy3 lipid derivatives which are incorporated into erythrocyte membranes. The fluorescent label incorporation and retention, erythrocyte circulation and immunocompatibility as a function of lipid structure are studied in vitro and in vivo.